Essence of success twelve mini biographies - edited by Anthony Brito (London Hyper Drive system, 2015)
This book is a compilation of twelve concise biographies of Richard Branson, Bill Gates, Nelson Mandela, Steven Spielberg, Stephen Hawking, Chris Evans, Frank Sinatra, Tony Blair, Imran Khan, Malcolm X, James Dyson and Margaret Thatcher, which will enable the reader to gain an insight into each character in one short sitting. Rather than reading an exhaustive 300 page book and becoming an expert on Bill Gates? life, for example, the reader can discover the essential character, motivation and philosophy of the individual in just a few hours. The idea is that during a lunch break or when winding down, you can get an accurate snapshot of someone?s entire life. ?A whole life without having to read a whole book.? This was the concept. But we could not resist investigating a further possibility. We had to ask the question: ?Is there a common factor between these 12 diverse success stories ?? We present a detailed analysis of each of the 12 lives in order to enable the reader to find any common character traits or common experiences shared between them that might have enabled them to succeed so spectacularly. The idea is that the essence of their success can be distilled from the diversity of their paths to find it. On completion of the mini-biographies, we actually realised what the common factor was. We discovered what could be the vital ingredient, the necessary ingredient for outstanding success. This is covered in our conclusion at the end of the book. The purpose of this book is to provide inspiration to the reader, and to explain that any person individual views and convictions are as important as the general consensus. No individual mind is inferior to any collection of minds. An individual can be right if they stand firm in the face of mass opposition. While our study is a contemporary one, we fully realise that the maverick spirit has been evident throughout history. Scientifically men such as Isaac Newton pushed the boundaries of human endeavour. In other eyes, religious figures such as Jesus provide the seminal example of an outsider who epitomised the maverick spirit. It is the realisation that ?the power of one? can make a difference within the world. As long as individuals follow their own unique calling and have the courage to act on their own initiative then the human race as a family, will continue to advance.
Keywords: Biographies